2019
DOI: 10.1158/1078-0432.ccr-18-2455
|View full text |Cite
|
Sign up to set email alerts
|

CAF-Derived IL6 and GM-CSF Cooperate to Induce M2-like TAMs–Letter

Abstract: In a recent article, Cho and colleagues highlight the connection between cancer-associated fibroblasts (CAF) and tumor-associated macrophages (TAM) in tumor progression. They show that cancer cell-activated CAFs induced monocyte differentiation into M2-like TAMs via IL6 and GM-CSF release, and that CAFs cotransplantation with tumor cells enhances TAM infiltration and the metastatic process in a syngeneic colon carcinoma mouse model (1).This and other recent evidence on CAFs/TAMs relationship (1-3) help to bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…Furthermore, CAF-derived IL-6 and GM-CSF cooperate to induce trans-differentiation of tumor-resident macrophages to M2 macrophages. 146 148 Therefore, the iCAFs are more likely the subpopulation that induces M2 polarization, although this will need to be verified by direct experimental evidence. In addition, the hypoxic tumor microenvironment can also triggers M2-polarized TAMs.…”
Section: Components Of Pdac Tumor Microenvironment (Tme) That Drive Ementioning
confidence: 99%
“…Furthermore, CAF-derived IL-6 and GM-CSF cooperate to induce trans-differentiation of tumor-resident macrophages to M2 macrophages. 146 148 Therefore, the iCAFs are more likely the subpopulation that induces M2 polarization, although this will need to be verified by direct experimental evidence. In addition, the hypoxic tumor microenvironment can also triggers M2-polarized TAMs.…”
Section: Components Of Pdac Tumor Microenvironment (Tme) That Drive Ementioning
confidence: 99%
“…We previously reported that treatment of pancreatic cancer heterotopic allografts with anti-BAG3 antibody down-modulated CAF activation and impaired the desmoplastic structure in pancreatic cancer stroma [ 13 ]. In agreement with results in heterotopic allografts, we observed a reduction of the expression of the activation marker α-SMA in CAFs.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in neoplastic cell cytosol it regulates autophagy [ 25 ] and interferes with the Hsp70-mediated delivery of IKKγ [ 9 ] and other anti-apoptotic proteins [ 15 ] to proteasome, sustaining their levels and cell survival, while, being secreted by pancreatic cancer cells, it binds to a specific receptor (BAG3R) on TAMs, triggering the p38- and Akt-dependent release of pro-tumorigenic cytokines and chemokines [ 10 , 11 , 15 ]. In several pancreatic cancer murine models, BAG3 blockade by a monoclonal antibody impairs the activation of TAMs [ 11 , 12 ] and CAFs [ 13 ]. This effect produces a significant reduction of the tumor growth of both MIA PaCa-2 and patient-derived pancreatic cancer xenografts in immunodeficient mice [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The eBAG3‐induced signaling in cells expressing BAG3R involves AKT phosphorylation, 8 which in turn is able to trigger downstream the expression of α‐SMA 19 . To verify the possible activity of eBAG3 on human fibroblasts, NHDF cells were incubated with rBAG3 and the effect on the expression of the fibroblasts' activation marker α‐SMA was then evaluated.…”
Section: Resultsmentioning
confidence: 99%